N17 Neck circumference as a practical tool for detecting visceral adipose tissue in Ulcerative Colitis patients. - V M Mendoza Martinez; M A Santoyo Chávez; E Rivera; R Baños Vazquez; D López-González; A L Almiray-Soto; J L De Leon Rendon; N Bueno Hernández (Journal of Crohn’s and Colitis, 2026)
Abstract Background Visceral adipose tissue (VAT) is a predictor of cardiovascular risk; its accumulation has been associated with various metabolic diseases such as metabolic syndrome and insulin resistance. Patients with ulcerative colitis (UC) are at cardiovascular risk due to medications and chronic inflammation 1. Waist circumference (WC) is a very useful anthropometric measurement associated with central adiposity; however, the presence of bloating or the use of ostomies can modify this measurement 2. Neck circumference (NC) has been proposed as a simple anthropometric marker associated with upper body adiposity and metabolic dysfunction 3. Furthermore, the waist-to-hip ratio (WHR) is a recognized indicator that allows for the evaluation of body fat distribution, particularly the accumulation of central adiposity 4. Aim: To evaluate the correlation between NC and anthropometric markers such as VAT, WC, ICC, BMI and blood pressure in patients with UC. Methods A cross-sectional analysis was performed in patients with UC. The VAT was obtained through dual-energy X-ray absorptiometry (DXA). Blood pressure was measured at rest for 10 minutes using a digital sphygmomanometer. Anthropometric measurements of height and weight were taken to calculate BMI, and all circumferences were measured with the patient standing upright. WC was measured between the midpoint of the iliac crest and the last rib; NC was measured with the head in the Frankfurt plane, placing the anthropometric tape horizontally below the laryngeal prominence; and hip circumference (HC) was measured at the point of greatest gluteal prominence, keeping the tape horizontal. The WHR was calculated by dividing WC by HC. Correlation analysis was performed using Spearman’s rank correlation coefficient. Results A total of 51 patients were included, where 57% were women and 43% men, most of them had an extension of pancolitis 56% and 45% were active according to the criteria of Truelove and Witts (Table 1). NC had a positive and moderate correlation with VAT (r = 0.608; p < 0.001), BMI (r = 0.518, p < 0.001), WHR (r = 0.585, p < 0.001) and a strong correlation with WC (r = 0.717, p < 0.001), in addition, correlation with systolic blood pressure (r = 0.412, p = 0.002) and a lower correlation with diastolic pressure (r = 0.270, p = 0.050). Conclusion NC was significantly associated with VAT in patients with UC. It can be an easy anthropometry measure to identify patients with cardiometabolic risk, especially when there are no tools for its measurement or in patients with bloating that WC is not so reliable (figure 1). Further studies are required to explore its predictive value in metabolic complications and cardiovascular outcomes in this population. References: 1. Soares CA, Fiuza JG, Rodrigues CAM, et al. Inflammatory bowel disease and cardiac function: a systematic review of literature with meta-analysis. Therap Adv Gastroenterol. 2024;17:17562848241299534. doi:10.1177/17562848241299534 2. Houghton LA, Lea R, Agrawal A, Reilly B, Whorwell PJ. Relationship of abdominal bloating to distention in irritable bowel syndrome and effect of bowel habit. Gastroenterology. Oct 2006;131(4):1003-10. doi:10.1053/j.gastro.2006.07.015 3. Wu Z, Huang Z, Sun L, et al. Neck circumference, waist-to-height ratio, Chinese visceral adiposity index and incident heart failure. Nutr J. Nov 28 2024;23(1):149. doi:10.1186/s12937-024-01048-7 4. Sun L, Zhang S, Pan J, et al. Central obesity measured by waist-to-hip ratio independently predicts crohn’s disease risk: a prospective cohort study. Lipids Health Dis. Oct 29 2025;24(1):348. doi:10.1186/s12944-025-02763-8 Conflict of interest: Mendoza Martinez, Viridiana Montsserrat: No conflict of interest Santoyo Chávez, Martha Alison: No conflict of interest Rivera, Ernestina: No conflict of interest Baños Vazquez, Roberto: No conflict of interest López-González, Desirée: No conflict of interest Almiray-Soto, Alma Lidia: No conflict of interest De Leon Rendon, Jorge Luis: No conflict of interest Bueno Hernández, Nallely: No conflict of interest